2011
DOI: 10.1007/s00127-011-0360-1
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and illness beliefs in individuals with early psychosis

Abstract: Causality has not been fully established, but these results suggest that beliefs about mental health problems may have a direct impact on outcome, and point towards possible targets for intervention, such as challenging illness-related appraisals. This is consistent with both general cognitive models of psychosis, and Cognitive Behaviour Therapy for this client group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 35 publications
2
19
0
Order By: Relevance
“…9,44,45 In terms of the clinical correlates of QOL, as expected, a number of subjective domains were influenced by depressive symptoms, and objective domains were influenced by negative symptoms, which is consistent with FEP studies to date. 3,4,6,8,16,46 There were moderate correlations between some objective QOL domains and premorbid adjustment that were not retained as significant in regression models predicting objective QOL. Our finding that DUP independently predicts QOL is consistent with some studies, 4,16,47 but some have also found premorbid adjustment as an independent predictor.…”
Section: Discussionmentioning
confidence: 98%
“…9,44,45 In terms of the clinical correlates of QOL, as expected, a number of subjective domains were influenced by depressive symptoms, and objective domains were influenced by negative symptoms, which is consistent with FEP studies to date. 3,4,6,8,16,46 There were moderate correlations between some objective QOL domains and premorbid adjustment that were not retained as significant in regression models predicting objective QOL. Our finding that DUP independently predicts QOL is consistent with some studies, 4,16,47 but some have also found premorbid adjustment as an independent predictor.…”
Section: Discussionmentioning
confidence: 98%
“…17 In FEP patients, poor sQoL has been generally related to negative and depressive symptoms, longer duration of untreated psychosis (DUP), poor premorbid adjustment and certain illness beliefs (e.g. Browne et al; 3 Priebe et al; 17 Malla et al; 18 Theodore et al; 19 Gomez-de-Regil et al; 20 ). In order to better understand the factors related to the worsening of sQoL in early psychosis, it is important to examine which features are already associated with poor sQoL in individuals presenting clinical high risk.…”
Section: Introductionmentioning
confidence: 99%
“…Although literature demonstrated that anxiety symptoms (Huppert and Smith, 2001;Braga et al, 2005), especially social anxiety (Pallanti et al, 2004;Kumazaki et al, 2012) which is the most prevalent comorbid anxiety condition in patients with psychotic disorders (Achim et al, 2011), were related to poorer SQoL in chronic schizophrenia, very few studies have been conducted to investigate the association between anxiety symptoms (and none for social anxiety) and SQoL in FEP. Further, most of these first-episode studies assessed anxiety symptoms by using either ratings of a single item (Theodore et al, 2012) or a symptom component score combining depression and anxiety items (Priebe et al, 2000;Melle et al, 2005;Gorna et al, 2008;MacBeth et al, 2015) selected from a general psychopathology scale. Such measurement lacks specificity to detect the influence of anxiety symptoms, in particular social anxiety, on SQoL.…”
mentioning
confidence: 99%